Molecular Characteristic and Virulence Gene Profiles of Community-Associated Methicillin-Resistant Staphylococcus aureus Isolates from Pediatric Patients in Shanghai, China - Wang, Xing; Li, Xia; Liu, Wei; Huang, Weichun; Fu, Qihua; Li, Min (Frontiers in Microbiology, 2016)
Staphylococcus aureus is a globally important human pathogen, especially among children and immunocompromised patients. The emergence and spread of community-associated methicillin-resistant S. aureus (CA-MRSA) has become a serious public health problem worldwide. The aim of this study was to investigate the prevalence, molecular characteristics and virulence profiles of CA-MRSA infections from pediatric patients in a university hospital in Shanghai, China. A total of 80 CA-MRSA isolates were collected from July 2012 to December 2013 in Shanghai Children's Medical Center and analyzed by multilocus sequence typing, staphylococcus chromosomal cassette mec (SCCmec) typing, and spa typing. The detection of Panton-Valentine Leukocidin (pvl), superantigenic and exfoliative toxins, and adhesin genes was also performed. Overall, 16 distinct sequence types (STs) were identified among the 80 isolates. Among them, ST59 was found to be the most prevalent, followed by ST398 (11.3%, 9/80) and ST88 (8.8%, 7/80). SCCmec types IV and V were observed, at 60 and 40%, respectively. Thirty spa types were identified, spa t437 (23.8%) was the most predominant type. All 80 isolates exhibited carriage of at least four virulence genes. Thirty-four (42.5%, 34/80) isolates harbored ≥10 tested virulence genes. Adhesion genes were present in most of the MRSA isolates, including the following: icaA (100%), clfA (100%), sdrC (95%), and sdrE (63.8%). The prevalence of pvl gene was 20%, and multidrug resistance was observed in 36% of all strains. In addition, ST59-MRSA-IV with t437 accounted for 21.3% of occurrences, making it the most prevalent clone. Isolates that were carriers of toxin genes, and hla (100%) and hlg (87.5%) were the most frequent. In conclusion, simultaneous carriage of multiple virulence genes and genetically considerable diversity were very common among CA-MRSA from pediatric patients in Shanghai. ST59-MRSA-IV with t437 was still the most predominant type. The combination of virulence gene profiles and antibiotic resistance may help ST59 to be successfully spread among children.